Chroniclers of light. The Oñate family photographers - Agustín Lacruz, Carmen; Clavero Galofré, Manuel (Revista General de Información y Documentación, 2020)
Oñate is the surname of a renowned family of photographers from Calatayud, formed by the brothers Santiago and Ricardo Oñate Pérez; Isabel Lafuente, Santiago’s second wife, known as “Oñate’s widow” and Mariano Oñate Malo and Santiago Oñate Lafuente, sons of Santiago. They starred in the first fifty years of the history of the photography in Calatayud, between 1870 and 1930, coinciding with the Bourbon Restoration and the reigns of Alfonso XII and Alfonso XIII. They were formed and worked in Calatayud and later also in Madrid, Aranjuez and Zaragoza, where they achieved fame and renown. The article analyzes the activity of the Oñate photographers. The places in which they worked are located, the context in which they did it and the work that has survived to this day is identified and described. The study has been carried out through the analysis of available archival and newspaper sources, as well as the systematic review of bibliographic information sources such as yearbooks and national, regional and local directories and telephone directories. Among the results achieved, the knowledge of their biographies, the contextualization of their professional careers and the characterization of their work stand out.